THE EXISTENCE OF MINANGKABAU MALE TAYLOR (Case Study Simpang Baru Market, Tampan District, Pekanbaru) - M. Aldo Malib; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pasar Simpang Baru was previously one of the traditional markets in Pekanbaru City. Initially, it was only a market for the surrounding environment, with limited facilities and infrastructure, namely in the form of kiosks, booths, and street vendors to accommodate and meet the needs of the surrounding community and under the authority of Tampan District. However, along with the development of Pekanbaru City, the Simpang Baru Market automatically grows to be as large as it is today, this is very helpful in meeting the needs of the growing community. One of the services available at Simpang Baru Market is the tailor. Especially male tailors whose tribe is Minangkabau. Of course, sewing activities that are usually carried out by women will be different if it is done by men. So it is necessary to have special research related to this phenomenon, especially how the tailors maintain their business existence. The purpose of this study is to determine the existence of Minangkabau male tailors in Pekanbaru and to determine the strategies adopted by Minangkabau male tailors. This study involved 4 respondents who were tailors. The results of this study indicate that of the 5 strategies that may be undertaken by tailors (biological, successive, educational, economic investment, and symbolic investment strategies), the tailors are more likely to use economic strategies to sustain their business. Keywords: Strategy, Male Tailor, Minangkabau